Factors Influencing Graft Choice in Revision Anterior Cruciate Ligament Reconstruction in the MARS Group - Group, MARS (The Journal of Knee Surgery, 2016)
It has not been known what drives revision anterior cruciate ligament (ACL) reconstruction graft choice in the past. We undertook this study to utilize the Multicenter ACL Revision Study (MARS) group and propensity score statistical analysis to determine the drivers of revision ACL reconstruction graft choice. We hypothesized that propensity analysis would demonstrate that individual surgeons still have significant impact on revision ACL reconstruction. Twelve hundred patients were enrolled in this longitudinal revision cohort by 83 surgeons at 52 sites. The median age was 26 years and 505 (42%) were females. One thousand forty-nine (87%) patients were undergoing their first ACL revision. Graft choice for revision ACL reconstruction for these patients was 48% autograft, 49% allograft, and 3% combination. The independent variables of this model included gender, age, ethnicity, body mass index, smoking status, sport, activity level, previous graft, revision number, surgeon, surgeon's opinion of failure, previous technical aspects, etc. Surgeons were defined as those who contributed more than 15 patients during the enrollment period. . We calculated a propensity score for graft type based on the predicted probability of receiving an allograft from a logistic regression model. Propensity scores demonstrated that surgeon, prior graft choice, and patient age each had significant influence on which graft type was chosen for the revision ACL reconstruction (p  < 0.0001). The revising surgeon had the largest impact upon graft choice: ∼ 5 times that of the second-most important factor (prior graft). If the prior graft type was an autograft, then an allograft was 3.6 times more likely to be chosen for the revision. This current study demonstrates that the individual surgeon is ultimately the most important factor in revision ACL reconstruction graft choice. Additional statistically significant influences of graft choice included age, gender, previous graft choice, ACL revision number, concurrent medial collateral ligament/posteromedial repair, and opinion of the previous failure. This demonstrates that if graft choice is determined to impact outcome then surgeons have the ability to change and determine the graft utilized.Level of Evidence Level II (prospective comparative study).
Keywords: ACL revision; propensity; graft choice; surgeon choice